2023
DOI: 10.1021/acs.iecr.3c01083
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Philic Imidazolium-Based Poly(Ionic Liquid) Composite Membranes for Enhanced CO2/N2 Separation

Abstract: Poly(ionic liquid) (PIL)-based membranes for CO2 removal attract increased interest due to the tunability of their chemical structure and processability of polymers. In this work, the IL cation of 1-vinylimidazole was selected as the polymeric backbone to connect the cyano- and carboxyl-based side chains to explore their effects. The synthesized PILs were blended with polyacrylamide (PAM) to prepare composite membranes by coating the mixed solutions on polysulfone (PSF) membranes. The CO2 permeance and CO2/N2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…As depicted in the above results for gas separation performances (see Figure ), the membranes of M1-M4 and also the EtOH-pretreated membranes exhibit better performances than membranes of M5-M8, thereby these membranes with higher separation performance were selected for comparison with other PIL-based membranes reported in the literature . It can be found that the membranes developed in this work are closer to the “Robeson upper bound”.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…As depicted in the above results for gas separation performances (see Figure ), the membranes of M1-M4 and also the EtOH-pretreated membranes exhibit better performances than membranes of M5-M8, thereby these membranes with higher separation performance were selected for comparison with other PIL-based membranes reported in the literature . It can be found that the membranes developed in this work are closer to the “Robeson upper bound”.…”
Section: Resultsmentioning
confidence: 52%
“…Moreover, the surface and cross-sectional morphologies of the representative composite membranes of M1 and M5 were observed by SEM as shown in Figure B–E. For reference, the SEM images for the pristine PSF membranes were reported in our previous work . The PSF support exhibits a porous structure on the top layer and comb-shaped microporous channels on the middle part of the cross-sectional morphology.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…wet dry dry (4) where W wet and W dry represent the weight of the membrane at the water uptake equilibrium state and when completely dry, respectively.…”
Section: Industrial and Engineeringmentioning
confidence: 99%
“…CO 2 is a prevalent greenhouse gas, and its environmental impact has become increasingly critical due to economic and industrial development. , Carbon capture, utilization, and storage (CCUS) is a vital technology for mitigating global climate change. , It is noteworthy that in 2022, the CO 2 emissions from the power industry accounted for 39.3% of the total CO 2 emissions . A significant portion of these emissions arises from fossil fuel combustion in coal-fired power plants.…”
Section: Introductionmentioning
confidence: 99%